Arabic Linguistic and Literary Approaches in Interpreting Educational Verses: A Study of The Tafsirs of Al-Misbah - Kafrawi Kafrawi; Zamsiswaya Zamsiswaya; Asmal May (Dinasti Publisher, 2025)
This study analyzes the implications of applying Arabic linguistic and literary principles in interpreting educational verses of Islam as expounded in Tafsir Al-Misbah by M. Quraish Shihab. The primary focus of this research is to examine how nahw, ?arf, and bal?ghah contribute to formulating the substantive meaning of educational verses and strengthening the epistemological construction of Islamic educational values in the Qur'an. Using a qualitative approach with a thematic study design, this research systematically analyzes linguistic aspects of educationally oriented verses in Tafsir Al-Misbah. The findings indicate that the integration of linguistic and literary approaches not only enriches the conceptual understanding of Islamic education in the Qur’an but also reveals the rhetorical, stylistic, and aesthetic dimensions of Qur'anic language, significantly deepening the educational messages. The novelty of this research lies in developing a linguistics-based tafsir paradigm as an innovative approach to Islamic Religious Education (PAI), integrating linguistic analysis with Islamic educational values to establish a more systematic, contextual, and applicable understanding. This approach has the potential to serve as a model for reformulating the PAI curriculum, particularly in Qur'anic-based Arabic language learning, to enhance Islamic literacy, foster critical understanding of educational verses, and internalize moral values in response to the challenges of globalization.